THE IMPLEMENTATION OF RELIGIOUS MODERATION VALUES IN STATE MADRASAH ALIYAH KEEROM PAPUA - amri, amri (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2022)
This study aims to explain the values of religious moderation applied in State Madrasah Aliyah (MAN) Keerom Papua. State Madrasah Aliyah Keerom is an islamic school located in the midst of the majority Christian population of Papua Province. However, the existence of Madrasah Aliyah Keerom has never been disturbed. In fact, the school welcomes non-Muslims who join to study in this school. This research uses a qualitative approach. The data were collected through interview, field observations and documentation. The results show that there are islamic moderation values that are applied at State Madrasah Aliyah Keerom, namely the attitude of cooperation between religious adherents in the madrasah environment (al- musawah), fairness (tawazzun), tolerance (tassamuh) and openness (tathawwur wa ibtikar).